Antigen Discovery for Next-Generation Pertussis Vaccines Using Immunoproteomics and Transposon-Directed Insertion Sequencing. (28th December 2022) - Gregg, Kelsey A; Wang, Yihui; Warfel, Jason; Schoenfeld, Elizabeth; Jankowska, Ewa; Cipollo, John F; Mayho, Matthew; Boinett, Christine; Prasad, Deepika; Brickman, Timothy J; Armstrong, Sandra K; Parkhill, Julian; et al.
Abstract: Background: Despite high vaccination rates, the United States has experienced a resurgence in reported cases of pertussis after switching to the acellular pertussis vaccine, indicating a need for improved vaccines that enhance infection control. Methods: Bordetella pertussis antigens recognized by convalescent-baboon serum and nasopharyngeal wash were identified by immunoproteomics and their subcellular localization predicted. Genes essential or important for persistence in the baboon airway were identified by transposon-directed insertion-site sequencing (TraDIS) analysis. Results: In total, 314 B. pertussis antigens were identified by convalescent baboon serum and 748 by nasopharyngeal wash. Thirteen antigens were identified as immunogenic in baboons, essential for persistence in the airway by TraDIS, and membrane-localized: BP0840 (OmpP), Pal, OmpA2, BP1485, BamA, Pcp, MlaA, YfgL, BP2197, BP1569, MlaD, ComL, and BP0183. Conclusions: The B. pertussis antigens identified as immunogenic, essential for persistence in the airway, and membrane-localized warrant further investigation for inclusion in vaccines designed to reduce or prevent carriage of bacteria in the airway of vaccinated individuals. Abstract : Acellular pertussis vaccines may be improved by adding antigens that target the bacterium for clearance by the immune response. We identified potential surface-exposed antigens, essential for persistence in the airway, that are recognized by convalescent baboon serum and nasopharyngeal wash.